2016
DOI: 10.1002/elps.201500489
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of human serum albumin in embryo culture media for in vitro fertilization using monolithic columns with immobilized antibodies

Abstract: Affinity depletion of abundant proteins such as HSA is an important stage in routine sample preparation prior to MS/MS analysis of biological samples with high range of concentrations. Due to the charge competition effects in electrospray ion source that results in discrimination of the low-abundance species, as well as limited dynamic range of MS/MS, restricted typically by three orders of magnitude, the identification of low-abundance proteins becomes a challenge unless the sample is depleted from high-conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…A recent report described a novel immunoaffinity‐based convective interaction media analytical column (CIMac) with specificity to HSA (CIMac‐αHSA) for the fast and automated protein depletion . The polymethacrylate CIMac monolithic column allowed relatively shorter analysis time than the traditional chromatographic supports.…”
Section: Methodologies Used To Reduce the Complexity Of Proteomic Sammentioning
confidence: 99%
“…A recent report described a novel immunoaffinity‐based convective interaction media analytical column (CIMac) with specificity to HSA (CIMac‐αHSA) for the fast and automated protein depletion . The polymethacrylate CIMac monolithic column allowed relatively shorter analysis time than the traditional chromatographic supports.…”
Section: Methodologies Used To Reduce the Complexity Of Proteomic Sammentioning
confidence: 99%
“…Depletion of high‐abundance proteins is one possible strategy that enables, or at least improves, analysis of certain low abundant proteins. Recent study demonstrated removal up to 94% of HSA from cell culture media, utilized for clinical embryo growth, with monolithic column containing immobilized anti‐HSA Ab . Upon depletion of HSA, the number of identified cellular proteins in the analysed medium by MS increased 50%.…”
Section: Monoliths For High‐throughput Protein Purification or Screeningmentioning
confidence: 99%
“…The CIMac-@Tf columns were successfully prepared according to procedure developed for immobilization of polyclonal antibody specific for human serum albumin [27] using a mAb specific for transferrin (@Tf) and a hydrazide column, as described in the paragraph Preparation of columns with immobilized @Tf. After antibody immobilization, we confirmed that the column is specific for Tf.…”
Section: Chromatographic Characterization Of Monolithic Columns and Amentioning
confidence: 99%